Human Mesenchymal Stem Cells Derived from Adipose Tissue and Umbilical Cord, in Combination with Acellular Human Amniotic Membranes, for Skin Healing Processes in Animal Models: a Systematic Review - Giraldo, Valentina; Mayorga, Guillermo; Saavedra, Karen; Esquivel, Diana; Torres, Salem; Gomez, Lina Andrea (Revista Mexicana de Ingenieria Biomedica, 2024)
This systematic review aims to document the available research evidence regarding using mesenchymal stem cells (MSCs) and acellular amniotic membranes (AAM) as scaffolds in the murine model for tissue regeneration. This research was developed by analyzing available information on databases like Google Scholar, Pubmed, Scopus, and Web of Science, using the following key terms ’’Human Stem Cells’’, ’’Amniotic membrane’’, ’’Wound healing’ ’ and ’’Animal model’’. A total of 519 articles published from January 2013 to March 2024 were found, but only 8 studies were included in this review, the inclusion criteria were as follows the use of human-derived stem cells (UCMSCs and ADMSCs) seeded in decellularized hAM, in murine models with induced wounds (incisions or burns); exclusion criteria: stem cells obtained from non-human origin, combination of human stem cells from different tissues, use of a different biological scaffold, and studies that not assess efficacy in skin regeneration. The main outcomes were decreased wound closure time, increased angiogenesis, remodeling and increase in extracellular matrix deposition, increased synthesis of growth factors and anti-inflammatory cytokines, and optimization of biomechanical properties. Moreover, one of the main findings was that combining these methods can improve the healing process in chronic wounds. The main bias was related to the inclusion of more studies that used ADMSC (5 of 8); additionally, there were differences in the animal model used, the induced wound, and the comparison of different variables between the studies. In conclusion, we found that the combination of MSCs and AAM as a bio-scaffold improves general tissue healing and regeneration.